Effect of the Histone Methyltransferase Specific Probe BRD4770 on Metabolic Profiling of the Endophytic Fungus Diaporthe longicolla - Nishad, Jay Hind; Singh, Arti; Bharti, Rajnish; Prajapati, Priyanka; Sharma, Vijay Kumar; Gupta, Vijai Kumar; Kharwar, Ravindra Nath (Frontiers in Microbiology, 2021)
The endophytic fungus Diaporthe longicolla was isolated from the stem of Saraca asoca (Roxb.) Willd., commonly known as Ashok plant in India and Sri Lanka. Since no reports are available regarding epigenetic modulations by BRD4770 in microbial entities, D. longicolla was treated with different concentrations of BRD4770 for this purpose and evaluated for its antioxidant and antibacterial potential against five human pathogenic bacteria, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus (MRSA), Shigella boydii, Klebsiella pneumoniae, and Escherichia coli. The crude extract obtained from cultures treated with 100 nM concentration of BRD4770 showed increased antioxidant activity and inhibition zone against S. aureus and MRSA, compared to the non-treated control. The composition of the non-treated and treated crude extract was analyzed, and induced compounds were identified with the help of Gas chromatography–mass spectrometry (GC-MS) and LC-ESI-MS/MS. LC-ESI-MS/MS analysis showed that berberine (antibacterial)-, caffeine-, and theobromine (antioxidant)-like compounds were induced in the BRD4770-treated crude extract. The presence of particular absorbance at a wavelength of 346.5 nm for berberine, 259.4 nm for caffeine, and 278.4 nm for theobromine in the reverse-phase high-performance liquid chromatography (HPLC) analysis of both BRD4770-treated crude metabolites and standard solution of the above compounds strongly supported the increased antibacterial and antioxidant activities that may be due to inducing the alterations in bioactivities of the BRD4770-treated culture.